THE DIFFERENCES IN METABOLIC SYNDROME PARAMETERS BETWEEN INDIVIDUALS WITH MENTAL HEALTH DISORDERS AND HEALTHY INDIVIDUALS: A COMMUNITY BASED COMPARATIVE STUDY - Saefurrohim , Muhamad Zakki; Azmiardi, Akhmad; Zainafree , Intan; Suci Susilastuti , Mustika (Quality : Jurnal Kesehatan, 2024)
Objectives: This study aimed to analyze the differences in metabolic health parameter values with mental health disorders (MHD). Methods: a total of 3725 respondents were included in this study. This study used secondary data from the Cohort Study of Non-Communicable Disease Risk Factors collected by interview method on permanent residents in Bogor City, Indonesia in 2018. Respondents with MHD if they experienced at least 6 symptoms out of 20 symptoms in the Self Reporting Questionnaire (SRQ) instrument. Independent variables included fasting blood sugar, post-loading blood sugar, total cholesterol, LDL, HDL, triglycerides, systolic blood pressure, diastolic blood pressure, and body mass index (BMI). Data were analyzed by Mann-Whitney test. Results: Significant differences between individuals with and without mental health disorders were observed in age (p-value=0.037), total cholesterol level (p-value=0.003), triglyceride level (p-value=0.000), LDL level (p-value=0.001), HDL level (p-value=0. 003), body weight (p-value=0.000), height (p-value=0.000), and BMI (p-value=0.050), however, there were no significant differences in fasting blood sugar levels, post-loading blood sugar levels, systolic blood pressure, and diastolic blood pressure. Conclusions: This study found significant differences in several metabolic health parameters between individuals with and without mental health disorders (MDD). Parameters that showed significant differences included age, total cholesterol, triglycerides, LDL, HDL, weight, height, and body mass index (BMI). In contrast, no significant differences were found in fasting blood sugar levels, post-load blood sugar levels, systolic blood pressure, and diastolic blood pressure